2021
DOI: 10.21203/rs.3.rs-315524/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The combination of serum BDNF, cortisol and IFN-gamma can effectively diagnose major depressive disorder

Abstract: Background Misdiagnosis and ineffective treatment are common in major depressive disorder (MDD) in current clinical practice, while the combination of various proteins involved in the pathogenesis of MDD may assist the correct diagnosis. The study aimed to explore whether the combination of serum inflammatory, stress, and neurotrophic factors could be helpful for the diagnosis of MDD, and to investigate the predictors associated with early symptom improvement. Methods Baseline serum levels of C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The 17 items in HAMD-17 were separated into five factors: HAMD-A/S, HAMD-W, HAMD-CD, HAMD-R, and HAMD-SLD (24). Out of the five factors, t-test analysis showed that HAMD-SLD score of the experimental group was decreased significantly following rTMS intervention (rTMS vs. sham group: 4.132 ± 0.151 vs. 3.588 ± 0.149, t = 2.570, p = 0.0112; see Figure 2C), while other factors did not reach statistical significance (rTMS vs. sham group: 6.868 ± 0.474 vs. 6.147 ± 0.333, t = 1.244, p = 0.216, for HAMD-A/S; 0.618 ± 0.0785 vs. 0.588 ± 0.0601, t = 0.298, p = 0.767 for HAMD-W; 6.353 ± 0.296 vs. 5.897 ± 0.282, t = 1.115, p = 0.267 for HAMD-CD; 9.324 ± 0.238 vs. 8.823 ± 0.279, t = 1.363, p = 0.175 for HAMD-R; see Figures 2D-G).…”
Section: Improvement Of Repetitive Transcranial Magnetic Stimulation ...mentioning
confidence: 99%
“…The 17 items in HAMD-17 were separated into five factors: HAMD-A/S, HAMD-W, HAMD-CD, HAMD-R, and HAMD-SLD (24). Out of the five factors, t-test analysis showed that HAMD-SLD score of the experimental group was decreased significantly following rTMS intervention (rTMS vs. sham group: 4.132 ± 0.151 vs. 3.588 ± 0.149, t = 2.570, p = 0.0112; see Figure 2C), while other factors did not reach statistical significance (rTMS vs. sham group: 6.868 ± 0.474 vs. 6.147 ± 0.333, t = 1.244, p = 0.216, for HAMD-A/S; 0.618 ± 0.0785 vs. 0.588 ± 0.0601, t = 0.298, p = 0.767 for HAMD-W; 6.353 ± 0.296 vs. 5.897 ± 0.282, t = 1.115, p = 0.267 for HAMD-CD; 9.324 ± 0.238 vs. 8.823 ± 0.279, t = 1.363, p = 0.175 for HAMD-R; see Figures 2D-G).…”
Section: Improvement Of Repetitive Transcranial Magnetic Stimulation ...mentioning
confidence: 99%
“…Thus, to better understand their pathophysiologies, the combined study of different systems and networks is required. In this regard, a recent paper by Chen et al finds that combining the results of serum BDNF, cortisol, and interferon-gamma could help in making an accurate diagnosis of MDD ( 31 ).…”
Section: Introductionmentioning
confidence: 99%